PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Sidik, Pajar; Suhono, Suhono (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
This study aims to determine the effect of profitability on tax aggressiveness, the effect of leverage on tax aggressiveness, and the effect of profitability and leverage on tax aggressiveness. The government can also use tax revenue to build and improve public infrastructure so as to improve people's welfare. Therefore, the government always tries to increase the tax target from year to year through various policies. Tax revenue plays an important role in supporting government operations, because the size of the tax revenue will determine the amount of the APBN. 100 samples were taken from 2015 to 2019 with annual data on ROA, Leverage and Tax Aggressiveness. The statistical method used in this research is multiple regression analysis, classical assumption test, descriptive statistical analysis, determination analysis and hypothesis testing. From the results of this study it is known that profitability has a negative effect on tax aggressiveness. Leverage has no effect on tax aggressiveness. Profitability and Leverage have an effect on Tax Aggressiveness.